The impact of mechanical shear on membrane flux and energy demand - Zsirai, T.; Qiblawey, Hazim; A-Marri, M. J.; Judd, Simon J. (Elsevier, 2016)
The use of forced mechanical shear for both disc membranes (rotating and vibrating disc filtration, RDF and VDF respectively) and hollow fibres (vibrating HF membranes, VHFM) is reviewed. These systems have been extensively studied and, in the case of the disc membranes, have reached commercialisation and proven effective in achieving transmembrane pressure (TMP) control for various challenging feed waters. The effects of operating conditions, namely shear rate as enhanced by rotation and vibration speed and TMP, and feed water quality on the filtration flux and specific energy consumption are quantified as part of the review. A new relationship is revealed between the two empirical constants governing the classical relationship between membrane flux and shear rate, and a mathematical correlation proposed accordingly. A study of available information on energy reveals that operation at lower shear rates (i.e. rotation or vibration speeds) and more conservative fluxes leads to lower specific energy demands in kWh m−3 permeate, albeit with a larger required membrane area.
Keywords: Mechanical shear; Rotating membranes; Vibrating membranes; Hollow fibre; Specific energy demand